Employment effects of CAP payments in the UK non-farm economy - Marian Rizov; Sophia Davidova; Alastair Bailey (European Review of Agricultural Economics, 2018)
This paper investigates the effects of the Common Agricultural Policy (CAP) payments on the indirectly generated non-farm jobs in small and medium-sized enterprises, which are central to job creation. It examines whether there are differences in the effect according to business location - rural or urban, the agricultural supply chain and according to CAP Pillars. A microeconomic approach is employed, based on firm data from FAME dataset combined with detailed subsidies information from Department of Environment, Food and Rural Affairs. The generalised method of moments (system GMM) is used to estimate the effect of CAP payments in both static and dynamic models of employment. The results suggest positive net spillovers of CAP payments to non-farm employment. Although the magnitude of the effect is small, it is economically significant. In general, Pillar 1 has a stronger positive employment effect relative to Pillar 2. However, Pillar 2 payments have a stronger positive effect per Euro spent in rural areas and within agricultural supply chain.
Keywords: D22; H25; J20; Q18; R11; 330; CAP; non-farm employment; SMEs; spillovers; rural–urban; system GMM